Effects of sports massage and intermittent cold-water immersion on recovery from matches by basketball players - Delextrat, A.; Calleja-Gonzalez, J.; Hippocrate, A.; Clarke, N. D. (Journal of Sports Sciences, 2013)
The aim of this study was to compare the effects of intermittent cold-water immersion and massage on perceptual and performance markers of recovery by basketball players after competitive matches. Eight men (age 23 ± 3 years; stature 190.5 ± 8.9 cm; body mass 90.3 ± 9.6 kg; body fat 12.8 ± 4.8%) and eight women (age 22 ± 2 years; stature 179.0 ± 8.5 cm; body mass 77.6 ± 9.2 kg; body fat 22.5 ± 6.6%) basketball players participated. Massage, cold-water immersion or control were applied immediately after competitive matches, followed by assessments of perceptual measures of recovery and physical performance, countermovement jump and repeated-sprint ability 24 h after intervention. There was lower perception of fatigue overall and in the legs immediately after the massage and cold-water immersion condition (P < 0.001; = 0.91). Furthermore, women had a lower perception of fatigue in cold-water immersion than massage at any testing time (P < 0.001; = 0.37). Jump performance was greater after cold-water immersion than the control condition (P = 0.037, = 0.37). There was no effect of any of the recovery interventions on repeated-sprint measures (P at best 0.067, at best 0.68). The results suggest that both massage and cold-water immersion improve perceptual measures of recovery. Furthermore, cold-water immersion improves jump performance although neither such immersion nor massage had an effect on repeated-sprint ability. This suggests that, overall, cold-water immersion is more useful than massage in the recovery from basketball matches, especially in women.